Implantation of BDNF-Producing Packaging Cells into Brain - Hidefumi Fukumitsu; Sayaka Takase-Yoden; Shoei Furukawa; Kiyomitsu Nemoto; Tomio Ikeda; Rihito Watanabe M.D. (Cell Transplantation, 2002)
In order to invent a screening system to check in vivo gene function and the efficiency of gene transfer mediated by a retroviral vector system, we established a novel packaging cell, PacC6/A8, that is transplantable to rat brains. The packaging cell is based on the gene of the neuropatogenic retrovirus, A8-V. For expression in the brain, a vector that expresses brain-derived neurotrophic factor (BDNF) tagged by c-Myc-His 6 (LxA/bdmh) was constructed. After transfection of LxA/bdmh to PacC6/A8, a cloned cell line, PacC6/ A8/bmh, was established. PacC6/A8/bmh cells stably produced pseudotyped retroviruses carrying LxA/ bdmh. For a control, a retroviral vector that bears the gene that codes enhanced green fluorescent protein (EGFP) tagged by C-Mic-His 6 was also created and used for the establishment of PacC6/A8/gfmh cells that produce pseudotyped retroviruses carrying LxA/gfmh. PacC6/A8/bmh and PacC6/A8/gfmh cells were injected to the brain of newborn rats. A tumor was formed in all the rats injected that did not exhibit any symptoms until 3–4 weeks after the injection. A histological study of the injected rats revealed that the transferred BDNF gene was expressed in the brain of rats injected with PacC6/A8/bmh cells, but not in rats with PacC6/A8/gfmh cells. Interestingly, many activated microglia had migrated into the tumor induced by PacC6/A8/bmh cells, and expressed a high amount of BDNF.